Sand Shape Analysis with Erosion on Hydraulic Turbine Material: A Case Study of Roshi Khola Nepal - Poudel, Laxman; Thapa, Bhola; Shrestha, Bim Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Hard particles as Quartz and Feldspar are present in large amount in most of the rivers across the Himalayan basins. In run-off-river hydro power plants these particles find way to turbine and cause its components to erode. Loss of turbine material due to the erosion and subsequent change in flow pattern induce several operational and maintenance problems in the power plants. Reduction in overall efficiency, vibrations and reduced life of turbine components are the major effects of sand erosion of hydraulic turbines. Sand erosion on hydraulic turbines is a complex phenomenon and depends upon several factors. One of the most influencing parameter is the characteristics of sediment particles. Quantity of sediment particles, which are harder than the turbine material, is one of the bases to indicate erosion potential of a particular site. Research findings have indicated that shape and size of the hard particles together with velocity of impact play a major role to decide the mode and rate of erosion in turbine components. It is not a common practice in Himalayan basins to conduct a detail study of sediment characteristics as a part of feasibility study for hydropower projects. Lack of scientifically verified procedures and guidelines to conduct the sediment analysis to estimate its erosion potential is one of the reasons to overlook this important part of feasibility study. These article present, Experimental studies have also been done to analyze the effects of shape and size of hard particles on turbine material. Efforts have also been given to develop standard procedures to conduct similar study to compare erosion potential between different hydropower sites. Digital image processing software and sieve analyzer have been utilized to extract shape and size of sediment particles from the erosion sensitive power plants. The experimental studies of sand erosion of different shapes and sizes of sediment particles on hydraulic turbine material have been conducted by High velocity test rig method at Kathmandu University. Twenty one different sediment shape samples and four different sand size range were studied to correlate the effects of sediment shape and size with the erosion of Hydraulic turbine material. It was observed that the shape of sediment particles have considerable effect on erosion of turbine material which is in between 0.000057 mg to 0.00031 mg and major percentage of abundance of the sand shape is 53, 20, 16 and 11 of circular, elongation, square and triangular respectively. In general Irregular shapes have more erosion potential than regular shapes. It was also observed that the particles with the irregular shape of smaller size induce higher erosion rates than that of the larger size with the different shape. These findings will help to select the proper site of a power plant in erosion prone basins and would also help to design suitable settling basins to trap sediment particles having higher erosion potentials.